A DESCRIPTION OF MEDICAL RECORD OFFICER'S EYE FAILURE IN THE FILLING ROOM OF KEDIRI BAPTIST HOSPITAL: GAMBARAN KELELAHAN MATA PETUGAS REKAM MEDIS DI RUANG FIILING RUMAH SAKIT BAPTIS KEDIRI - jayanti, Krisnita Dwi Jayanti (Journal Health Information Management Indonesian (JHIMI), 2023)
Good and correct lighting can help workers concentrate more at work, and if the lighting in the room is not in accordance with the type of work it can cause eye fatigue for workers. Eye fatigue is a symptom caused by the excessive effort of the visual system that is in less than perfect conditions to obtain sharpness. The purpose of this study is to know the picture lighting intensity in the medical records portion filling and the knowing eyestrain picture medical records clerk in the room-filling Home Sick Baptis Kediri. This study uses a descriptive survey and uses an approach cross-sectional, with a sample of 5 people filing data collection using observations and questionnaires that were filled out by the respondents themselves. The sampling technique is the method of the total population. The results showed that the lighting intensity in the filling room was still below the standard, namely 58 lux, where 3 officers experienced eye fatigue. Conclusion The lighting in the filling room of Baptis Hospital Kediri is still below the standard, namely 58 lux, where the lighting standard is not in accordance with the Decree of the Minister of Health Number 1405/Menkes/SK/XI/2002 regarding the type of routine work. Complaints of Eye Fatigue, as many as 3 people who work in the filling room experience complaints of eye fatigue. Suggestions should be replaced with brighter lights. And do eye relaxation.